2020
DOI: 10.21203/rs.3.rs-17231/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared Decision-making between health care providers and patients at a Tertiary Hospital Diabetic Clinic in Tanzania

Abstract: Background Patients’ participation in decision making regarding their treatment is defined in ethical, legal and human rights standards in the provision of care that concerns health providers and the entire community. This study was conducted to document experiences of patients and health care providers on shared decision making. Methods:This study employed a phenomenological study design using in-depth interview technique. Study participants were diabetic patients visiting the clinic and healthcare providers … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…A study on the experiences of diabetic patients and healthcare providers on shared decision-making conducted in Tanzania found that neither the patients nor the healthcare providers had been using decision-making aids; the patients reported that only health education tools are being used for educating them. [48]…”
Section: Discussionmentioning
confidence: 99%
“…A study on the experiences of diabetic patients and healthcare providers on shared decision-making conducted in Tanzania found that neither the patients nor the healthcare providers had been using decision-making aids; the patients reported that only health education tools are being used for educating them. [48]…”
Section: Discussionmentioning
confidence: 99%
“…SDM has emerged as a policy issue in developed countries such as Canada, Australia, the UK, the USA, France, Germany, and Italy (Coulter, 2017). However, in developing countries, the implementation of SDM has faced challenges such as users’ health literacy, available time and resources, physician's communication style or attitude, and whether users are accustomed to taking a passive role (Kruk et al, 2018; Tong et al, 2017; Tong et al, 2020; Vedasto et al, 2021).…”
Section: Interprofessional Approachmentioning
confidence: 99%
“…Several practical factors may serve as barriers to respect for patient autonomy, particularly in resource-constrained environments, such as lack of training in facilitating shared decision making, poor communication skills, and limited clinician time. 56,58,59 Additional strategies may also be needed to address language barriers, low health literacy, or cultural norms that discourage conversations about death or end-of-life care. 58,59 Factors that generally impede access to health services for patients may limit their ability to engage with available opportunities for shared decision making or health education.…”
Section: Practical Barriers To Respecting Patient Autonomy Via Shared Decision Makingmentioning
confidence: 99%
“…56,58,59 Additional strategies may also be needed to address language barriers, low health literacy, or cultural norms that discourage conversations about death or end-of-life care. 58,59 Factors that generally impede access to health services for patients may limit their ability to engage with available opportunities for shared decision making or health education.…”
Section: Practical Barriers To Respecting Patient Autonomy Via Shared Decision Makingmentioning
confidence: 99%